2014
DOI: 10.1007/s40262-014-0135-4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Morphine Dosing for Postoperative Neonates and Infants

Abstract: Morphine paediatric dosing algorithms corrected for pharmacokinetic differences alone yield effective doses that prevent over-dosing for neonates with a PNA <10 days. The fact that many neonates and infants with a PNA ≥10 days still required rescue medication warrants pharmacodynamic studies to further optimize the dosing algorithm for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 17 publications
3
72
0
Order By: Relevance
“…Figure 4 shows the relation between postoperative morphine dosages in our research population (except for in those who died within 72 h after surgery) and the morphine dosages calculated according to the PK/PD model of Krekels et al [17]. This validated model is based on term newborns that undergo major noncardiac surgery and receive a loading dose of 100 μg/kg in the operating room.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 4 shows the relation between postoperative morphine dosages in our research population (except for in those who died within 72 h after surgery) and the morphine dosages calculated according to the PK/PD model of Krekels et al [17]. This validated model is based on term newborns that undergo major noncardiac surgery and receive a loading dose of 100 μg/kg in the operating room.…”
Section: Resultsmentioning
confidence: 99%
“…The advised morphine dosages according to the PK/PD model of Krekels et al [17], based on the birth weight and postnatal age, were also calculated.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While pediatric dosing regimens are mostly empirically derived using extrapolations based on body weight (2,3), it has been shown before that dosing in children should be guided by the understanding of developmental changes in the pharmacokinetic and/or pharmacodynamic relation of drugs (2,4,5). More specifically, translation of results from pharmacokinetic modeling studies has been shown to result in individualized dosing guidelines for many different drugs in pediatric clinical practice (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%